A trait of mind: stability and robustness of sleep across sleep opportunity manipulations during simulated military operational stress. Issue 2 (25th August 2021) - LaGoy, Alice D; Cashmere, J David; Beckner, Meaghan E; Eagle, Shawn R; Sinnott, Aaron M; Conkright, William R; Miller, Eric; Derrow, Carson; Dretsch, Michael N; Flanagan, Shawn D; Nindl, Bradley C; Connaboy, Christopher; et al.
Abstract: Study Objectives: Within-subject stability of certain sleep features across multiple nights is thought to reflect the trait-like behavior of sleep. However, to be considered a trait, a parameter must be both stable and robust. Here, we examined the stability (i.e. across the same sleep opportunity periods) and robustness (i.e. across sleep opportunity periods that varied in duration and timing) of different sleep parameters. Methods: Sixty-eight military personnel (14 W) spent 5 nights in the sleep laboratory during a simulated military operational stress protocol. After an adaptation night, participants had an 8-hour sleep opportunity (23:00–07:00) followed by 2 consecutive nights of sleep restriction and disruption which included two 2-hour sleep opportunities (01:00–03:00; 05:00–07:00) and, lastly, another 8-hour sleep opportunity (23:00–07:00). Intra-class correlation coefficients were calculated to examine differences in stability and robustness across different sleep parameters. Results: Sleep architecture parameters were less stable and robust than absolute and relative spectral activity parameters. Further, relative spectral activity parameters were less robust than absolute spectral activity. Absolute alpha and sigma activity demonstrated the highest levels of stability that were also robust across sleep opportunities of varying duration and timing. Conclusions: Stability and robustness varied across different sleep parameters, but absolute NREM alpha and sigma activity demonstrated robust trait-like behavior across variable sleep opportunities. Reduced stability of other sleep architecture and spectral parameters during shorter sleep episodes as well as across different sleep opportunities has important implications for study design and interpretation.